KAJIAN KARAKTERISTIK PERJALANAN TRANSPORTASI RUTE ULU SIAU-MANADO - Barakati, Manginsihi Karel; Sompie, Bonny F.; Sendow, Theo Kurniawan (JURNAL ILMIAH MEDIA ENGINEERING, 2012)
Indonesia is an archipelago country brings a logic consequence in transportation that is coming up the traffic movement inter island to fulfill the need of goods and service. Like happen to the movement of Ulu Siau-Manado which is geographically the area located in North Sulawesi province which separated by the ocean. The transportation’s connection to reach Ulu Siau until now, it’s only using ocean line, by using moda ship transportation. The objectives of this research is to find out the factors which influenced toward the chosen of transportation moda for the proper trip’s route of Ulu Siau-Manado developed in the study area.The methodology used were qualitative and quantitative with stated preference method. The data were collected by interview and observation. The sample was taken 200 from the member of respondence from the ship passangers of Ulu Siau-Manado route. The data were analyzeddescriptively with proportion model, difference model, and ratio model. Calibration model was done by multiply regresion analyze.From the research it can be concluded that speed ship transportation moda became the first chosen of passangers. Followed by to keep the speedy, safety, and comfortable factors which already have on speed ship.